Increase in migraine diagnoses and guideline-concordant treatment in veterans, 2004–2012. (January 2017) - Altalib, HH; Fenton, BT; Sico, J; Goulet, JL; Bathulapalli, H; Mohammad, A; Kulas, J; Driscoll, M; Dziura, J; Mattocks, K; Kerns, R; Brandt, C; et al.
Background and aim: Health administrators, policy makers, and educators have attempted to increase guideline adherence of migraine medications while reducing inappropriate use of opioid- and barbiturate-containing medications. We evaluated the burden of migraine and proportion of guideline-concordant care in a large, national health care system over time. Methods: We conducted a time-series study using data from the Veterans Health Administration (VHA) electronic health record. Veterans with migraines were identified by ICD-9 code (346.X). Prescriptions and comorbid conditions were evaluated before and after migraine diagnosis. Chi-square tests and logistic regression were performed. Results: A total of 57, 064 veterans were diagnosed with migraine headache (5.3%), with women significantly more likely diagnosed (11.6% vs. 4.4%, p  < 0.0001). The number of veterans diagnosed with migraine has significantly increased over the years. By 2012, triptans were prescribed to 43% of people with migraine, with no difference by gender. However, triptan prescriptions increased from 2004 to 2012 in men, but not women, veterans. Preventive medicines showed a significant increase with the year of migraine diagnosis, after controlling for age, sex, race, and for comorbidities treated with medications used for migraine prevention. Conclusions: The burden of migraines is increasing within the VHA, with a corresponding increase in the delivery of guideline-concordant acute and prophylactic migraine-specific medication.